Cross-cultural engagement through translated news: A reception analysis. (July 2022) - Scammell, Claire; Bielsa, Esperança
Scholars in journalism and media studies have reflected on the cosmopolitan potential of the media and of news in particular to facilitate cross-cultural engagement. However, the key mediating role that translation plays when the news crosses linguistic and cultural borders has remained largely unexamined. This article considers how different translation strategies can maximise or minimise the potential journalism holds to facilitate cross-cultural engagement and approaches the still widely unexplored area of the reception of translated news. It relates existing debates in the discipline of translation studies to current approaches to the domestication of news in journalism research, paving the way for synergetic research across traditional disciplinary boundaries. The article explores how the news has the potential to equip readers with the cultural competence they need in a world that they share with others they do not understand, but only if journalistic translation practices promote rather than prevent engagement with the foreign cultural context. It discusses the findings of an exploratory focus-group study that compares the response of readers to news reporting translated according to the current norm for domesticating translation strategies with the response of readers to the same reports translated using an experimental 'foreignised' approach. The focus-group investigation, which takes Reuters' English-language reporting on news from France as a case study, finds indications that the foreignised approach, by exposing the reader to the foreign cultural specificity rather than domesticating the news information using terms available in the target culture and language, is successful in facilitating cross-cultural engagement.